Diversity of Nuclear Lamin A/C Action as a Key to Tissue-Specific Regulation of Cellular Identity in Health and Disease - Malashicheva, Anna; Perepelina, Kseniya (Frontiers in Cell and Developmental Biology, 2021)
A-type lamins are the main structural components of the nucleus, which are mainly localized at the nucleus periphery. First of all, A-type lamins, together with B-type lamins and proteins of the inner nuclear membrane, form a stiff structure—the nuclear lamina. Besides maintaining the nucleus cell shape, A-type lamins play a critical role in many cellular events, such as gene transcription and epigenetic regulation. Nowadays it is clear that lamins play a very important role in determining cell fate decisions. Various mutations in genes encoding A-type lamins lead to damages of different types of tissues in humans, collectively known as laminopathies, and it is clear that A-type lamins are involved in the regulation of cell differentiation and stemness. However, the mechanisms of this regulation remain unclear. In this review, we discuss how A-type lamins can execute their regulatory role in determining the differentiation status of a cell. We have summarized recent data focused on lamin A/C action mechanisms in regulation of cell differentiation and identity development of stem cells of different origin. We also discuss how this knowledge can promote further research toward a deeper understanding of the role of lamin A/C mutations in laminopathies.